Faktor-Faktor Yang Mempengaruhi Tingkat Kelelahan Kerja Pada Pegawai di Balai Besar Kekarantinaan Kesehatan Kota Makassar - Syamsudin Suaebu; Rostina Rostina; Andi Ruhban; Farah Dwi Maghfirah (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2026)
One issue related to occupational health and safety is work-related fatigue. Work-related fatigue is an occupational health problem that can reduce productivity and increase the risk of workplace accidents. Therefore, work fatigue is a primary concern in the field of Occupational Health and Safety (OHS). This study aims to analyze the factors influencing the level of work fatigue among employees of the Makassar City Health Quarantine Center (BBKK), specifically in the work area of Sultan Hasanuddin Airport in Makassar, Maros. The study employed a cross-sectional design. A sample of 77 respondents was selected using simple random sampling based on the Slovin formula. Quantitative data were collected via a questionnaire; work-related fatigue was measured using the 30-item Industrial Fatigue Research Committee (IFRC) scale, sleep quality using the Pittsburgh Sleep Quality Index (PSQI), and a structured questionnaire for other variables. Qualitative data were obtained through in-depth interviews with four respondents. Quantitative analysis used the Chi-Square test, Fisher’s Exact Test, and calculation of the odds ratio (OR) with a 95% confidence interval; qualitative data were analyzed thematically. The results of the study indicate that age (p=0.458), length of service (p=0.140), working hours (p=0.856), and sleep quality (p=0.096) do not significantly influence the level of work-related fatigue. Based on these findings, it can be concluded that age, tenure, working hours, and sleep quality are not associated with levels of work fatigue. As a recommendation, future researchers are advised to pay attention to data collection methods, workplace climate measurement, and to use more specific instruments to measure work fatigue.